A Novel Approach of Partial Derivatives to Estimate the Normal Boiling Temperature via Viscosity Arrhenius Behaviour in N,N-Dimethylformamide + Ethanol Fluid Systems - Dallel, Mohamed; Al-Arfaj, Ahlam A.; Al-Omair, Nuhad A.; Alkhaldi, Mishael A.; Alzamel, Noura O.; Al-Zahrani, Asala A.; Ouerfelli, Noureddine (Asian Journal of Chemistry, 2017)
The experimental values of absolute viscosity in N,N-dimethylformamide + ethanol binary fluid mixtures (from 303.15 to 323.15 K) can induce us to investigate different correlation expressions as well as their derivative quantities. Investigation of the molar enthalpy of viscous flow (DH*) and the viscosity activation energy (Ea) reveals close values and similar variation against composition, here we can justify the notion of partial activation energies Ea1 and Ea2 for pure components along with their separately individual contributions. Correlation between the two Arrhenius parameters in the whole range of compositions shows the existence of different interaction behaviours, delimited by peculiar compositions. It is also noticed that the ratio between the two parameters leads to the Arrhenius temperature which is in causal correlation with the temperature of vapourization in the liquid-vapour isobaric diagram and the limiting partial properties can permit us to predict values of the boiling temperatures of the pure fluid components.